2008
DOI: 10.1111/j.1532-5415.2007.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Childhood Abuse on the Quality of Life and Health of Older People: Results from the Depression and Early Prevention of Suicide in General Practice Project

Abstract: The effects of childhood abuse appear to last a lifetime. Further research is required to improve understanding of the pathways that lead to such deleterious outcomes and ways to minimize its late-life effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
160
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(179 citation statements)
references
References 36 publications
12
160
1
3
Order By: Relevance
“…Similarly, another cross-sectional survey, which included data on 53,998 individuals from the USA, found increased ORs for diabetes, myocardial infarction and stroke depending on the number of adverse childhood events reported (Gilbert et al, 2015). The same holds true for a cross-sectional study with an Australian sample of more than 21,000 participants, showing increased ORs for stroke or myocardial infarction and emphysema if a person had experienced either physical or sexual abuse during childhood, while the odds increased further when both sexual and physical abuse had been experienced (Draper et al, 2008). This cumulative association was also shown for COPD and diabetes, where the odds were highest when both child physical and sexual abuse had been experienced (Shields, Hovdestad, Gilbert et al, 2016; Shields, Hovdestad, Pelletier et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Similarly, another cross-sectional survey, which included data on 53,998 individuals from the USA, found increased ORs for diabetes, myocardial infarction and stroke depending on the number of adverse childhood events reported (Gilbert et al, 2015). The same holds true for a cross-sectional study with an Australian sample of more than 21,000 participants, showing increased ORs for stroke or myocardial infarction and emphysema if a person had experienced either physical or sexual abuse during childhood, while the odds increased further when both sexual and physical abuse had been experienced (Draper et al, 2008). This cumulative association was also shown for COPD and diabetes, where the odds were highest when both child physical and sexual abuse had been experienced (Shields, Hovdestad, Gilbert et al, 2016; Shields, Hovdestad, Pelletier et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Depending on the number of maltreatment experiences encountered, the odds ratio (OR) was reported to be increased by up to 1.6 for severe obesity, 2.2 for ischaemic heart disease, 1.9 for the occurrence of any kind of cancer, 2.4 for stroke, 3.9 for chronic bronchitis or emphysema and 1.6 for diabetes (Felitti et al, 1998). Other extended cross-sectional studies followed, confirming associations of child maltreatment with an enhanced risk for obesity, hypertension, diabetes, emphysema and cardiovascular diseases, including stroke and myocardial infarction (Afifi, Mota, MacMillan, & Sareen, 2013; Draper et al, 2008; L. K. Gilbert et al, 2015). …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…They recorded (yes/no) whether they had lost a parent or had been victims of physical or sexual abuse before they were aged 15 years ("Were you the victim of physical or sexual abuse before you were 15 years old?") (Draper et al, 2008), and rated their overall health (fair/poor compared with good to excellent), their experience of pain (not at all or a little vs. quite a bit to extreme pain that interfered with work during the preceding four weeks) (the latter two questions are part of the Health Survey SF-12) (Ware et al, 2002), and reported whether they had been advised by their doctor that they had had depression, anxiety, diabetes, hypertension, a heart attack, or a stroke (i.e., doctor-made diagnosis).…”
Section: Other Study Measuresmentioning
confidence: 99%
“…Some proximal factors, like bereavement (Brilman and Ormel, 2001), may have a close temporal relationship with the onset of depressive symptoms, whereas remote factors, such as childhood abuse (Bradley et al, 2008;Draper et al, 2008) and limited formal education (Almeida et al, 2006;Ladin, 2008), may confer vulnerability even later in life. Lifestyle may also play a role: both past and current smoking have been associated with greater odds of depression , and so have physical inactivity (Kritz-Silverstein et al, 2001;Strawbridge et al, 2002), obesity (Almeida et al, 2009a) and heavy alcohol use (Bolton et al, 2009;Hamalainen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%